Pengaruh Revitalisasi Pasar Dan Modal Usaha Terhadap Pendapatan Pedagang Di Pasar Tradisional Kebon Roek Kota Mataram - Syahrul Sam; I Made Murjana; Surahman Hidayat (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This research aims to determine the effect of partial and simultaneous market revitalization and business capital on traders' income at the Kebon Roek traditional market, Mataram City. Therefore, the variable of this research consists of 2 (two) independent variables, namely Market Revitalization (X1), and Business Capital (X2) and the dependent variable is Income (Y). The population of this research was all permanent traders at Kebon Roek Market at the time this research was conducted, totaling 983 traders. Data were analyzed using Multiple Linear Regression. The results of this research show that Market Revitalization has a partially positive and significant effect on income with a calculated t value (10.72) greater than the t table value (1.291). Another result is that the variables Market Revitalization (X1) and Business Capital (X2) have a significant effect simultaneously with the calculated f value (294.54) being greater than the f table value (3.10) and a significance value of 0.000. The results of this research also show that the independent variables (Market Revitalization and Business Capital) are able to explain the dependent variable (Income) by 85.0%. Meanwhile, the remaining 15.0% of income is influenced by other variables outside the regression model.